2004
DOI: 10.1007/s00431-004-1503-0
|View full text |Cite
|
Sign up to set email alerts
|

Irritable bowel syndrome: the commonest cause of recurrent abdominal pain in children

Abstract: Of children presenting with recurrent abdominal pain in a hospital setting, 30% have a diagnosable organic aetiology compared to 8% in Apley's time. Irritable bowel syndrome, however, may be the commonest cause of recurrent abdominal pain and should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 21 publications
3
46
0
8
Order By: Relevance
“…RAP is a symptom based pediatric classification, with at least three attacks of abdominal pain during three consecutive months that interferes with daily activity, which includes a higher percentage of patients who also meet IBS diagnostic criteria. 19,53 In a sample of 21 RAP cases, Dufton, et al 18 found no differences in cold-pressor tolerance or pain intensity, which is consistent with our findings and those of Williams et al cited above. In a small sample including 20 RAP cases, Zohsel, et al found no difference in heat pain threshold or pressure pain threshold between cases and controls.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…RAP is a symptom based pediatric classification, with at least three attacks of abdominal pain during three consecutive months that interferes with daily activity, which includes a higher percentage of patients who also meet IBS diagnostic criteria. 19,53 In a sample of 21 RAP cases, Dufton, et al 18 found no differences in cold-pressor tolerance or pain intensity, which is consistent with our findings and those of Williams et al cited above. In a small sample including 20 RAP cases, Zohsel, et al found no difference in heat pain threshold or pressure pain threshold between cases and controls.…”
Section: Discussionsupporting
confidence: 92%
“…Thus there is a risk of misclassifying organic diseases as IBS. Still, with the knowledge that most pediatric patients with abdominal pain have functional gastroenterological disorders, 10,30,53 and that IBS is the most common cause, 19 the risk of misclassification is most likely acceptably low if typical symptoms of IBS are present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 It affects 10-20% of adolescents and adults in western societies 3 and is the commonest cause of recurrent abdominal pain in children. 4 IBS is defined by a symptom complex which includes abdominal pain and altered bowel function in the form of diarrhea, constipation, a sensation of fullness following evacuation, bloating or the passage of mucus per rectum. There are no physical or laboratory findings which are specific for IBS and the diagnosis is therefore based on symptomatology.…”
mentioning
confidence: 99%
“…[3][4][5] Avrupa'da çocuklarda fonksiyonel karın ağrısının en sık nedeni olarak irritabl barsak sendromu (İBS) bildirilirken, gelişmekte olan ülkelerde TKA olan çocukların %30'unda organik bir neden saptanmıştır. [6][7][8] Organik nedenler dışlandığında FGİB tanısına yönelinmektedir. Birçok farklı çalışmada, gastrointestinal parazitozlar, inflamatuar barsak hastalığı, çölyak hastalığı, Helicobacter pylori enfeksiyonu, üriner sistem enfeksiyonları, laktoz intoleransı, fruktoz intoleransı ve besin allerjilerinin TKA'ya yol açabilecek organik bir neden olabileceği kabul edilmiş; ancak hangi testin ne zaman, kime uygulanması gerektiği konusunda henüz bir fikir birliğine varılamamıştır.…”
unclassified